POTRET POLITIK EKONOMI ISLAM DI INDONESIA ERA REFORMASI - Nur Kholis (Millah: Journal of Religious Studies, 2011)
The artide below traces to analize the relationship between state (Indonesia) and the islamic economics in the term influence of the islamic political economy of Indonesian government to the development of Islamic economic practice in the society, especially at the reformation era. The artide find that the influence of Indonesian state with its political economy oriented to Islamic economic system in developing Islamic economic practice is very signifinace. It shows that there is a rapid progress of Islamic economic practice in the area of Islamic banking, Islamic insurance, Islamic capital market; Syariah Obligation, Islamic unit trust/mutual fund, and Islamic microfinance institution, and Islamic public finance after the state (Indonesia) support them in many ways, especially by formal regulation.